UNDERSTANDING THE ROLE OF IMMUNOMETABOLITE ITACONATE IN THE REGULATION OF HEPATIC LIPID METABOLISM DURING SEPSIS - Mainali, Rabina (Wake Forest University, 2023)
Sepsis is a life-threatening clinical complication with increased uncontrolled host immune response to an infection, mortality, morbidity, and financial burden worldwide. There has been a significant focus on understanding the role of metabolic reprogramming in the immune compartment during sepsis. However, there is a notable gap in our knowledge regarding the involvement of other vital organs responsible for maintaining metabolic integrity. Thus, the purpose of this work is to first expand our current understanding of how critical organs such as the liver contribute to preserving metabolism in the context of sepsis. In Chapter II, employing multi-omic approaches, we first demonstrate that mitochondrial reprogramming underlies impairment in energy production, remodeling of the TCA cycle, and an increase in oxidative stress, leading to the onset of dyslipidemia in the context of sepsis. Furthermore, the restoration of the pyruvate dehydrogenase complex (PDC) using dichloroacetate (DCA) improves hepatic metabolic dysfunction by enhancing the conversion of pyruvate to acetyl-CoA, highlighting the consequences of hepatic metabolic reprogramming.One major limitation of Chapter II was the lack of understanding regarding the molecular regulators driving the observed alterations in hepatic lipid metabolism. Therefore, our subsequent goal was to identify and investigate novel molecular interactions governing the dysregulation of lipid metabolism. Consequently, through analysis of the unbiased metabolomics dataset generated in Chapter II, we identified itaconate as the top accumulated hepatic metabolite produced in response to sepsis. However, understanding of itaconate’s anti-inflammatory and immunometabolic activities in response to infections is mostly limited to immune cells making it pertinent to explore its functional role in central organs critical to maintaining systemic metabolism. Hence, to gain further insight into its physiological role in the liver during sepsis, we subjected wild-type (WT) and global Irg1 knockout (KO) mice to septic conditions. In conjunction with our previous findings, we observed that WT septic mice develop hepatosteatosis. Interestingly, Irg1 knockout mice also develop this phenotype but to a more severe extent compared to WT counterparts in response to sepsis. For the first time, our data revealed itaconate as an important negative regulator of hepatic lipid accumulation in the context of sepsis. However, the exact molecular mechanism by which itaconate interacts with regulators of hepatic lipid metabolism during sepsis is yet to be uncovered. Therefore, our next objective was to investigate the role of itaconate in modulating hepatic lipid metabolism during overt inflammation. In Chapter IV our data revealed that itaconate plays a significant role in enhancing lipid clearance in hepatocytes by stabilizing the mitochondrial fatty acid uptake enzyme known as CPT1a. Additionally, proteomic analysis of hepatic substrates of itaconate has identified novel substrates involved in protein ubiquitination, which we hypothesize contributes to its ability to promote lipid clearance. Furthermore, we observed that mice lacking Irg1 also display impaired systemic fatty acid utilization ability and thermogenesis in response to sepsis. In conclusion, our study contributes to the expanding understanding of itaconate as a metabolic regulator in non-immune cells in response to inflammation. These findings shed light on the mechanisms underlying hepatic lipid metabolism during sepsis and highlight the potential therapeutic implications of targeting itaconate in the management of sepsis-related complications such as dyslipidemia.